Water Soaking and Re-Drying Effect on Mechanical and Wear Properties of Nanoclay-Polyester Nanocomposites - Kini,Achutha (2022)
Abstract This research aims to investigate the influence of water soaking and re-drying on the mechanical and wear properties of nanoclay-polyester nanocomposites (NPNCs). The nanoclay addition significantly enhances the mechanical properties of NPNCs in as-made, water-soaked and re-dried conditions. Also, the addition of nanoclay decreased the percentage of reduction in mechanical properties under water-soaking condition. Re-drying recovers more than 90% in values of mechanical properties compared to original values. In contrast, the addition of nanoclay reduces the mass loss (wear test) of specimens in all three conditions. Re-dried specimens have lesser mass loss than water-soaked specimens and greater mass loss than as-made specimens. SEM images illustrate that the absorbed water can alter the fracture and worn-out surface by swelling and plasticization. Also, SEM images reveal that re-drying can reverse the effect of swelling and plasticization of the specimens.